From Content to Trust: How Short-Video Marketing and AI Tools Drive SME Performance on TikTok and Shopee - azizah, Fathia Azizah; Shintia, Novi; Rochmah, Siti (Program MM Universitas Surabaya, 2026)
Purpose: This study aims to examine how short-video marketing and AI content tools influence SME business performance on TikTok and Shopee through the mediating role of digital trust. The novelty of this research lies in integrating short-video marketing and AI-assisted content creation within a single trust-based explanatory model in the context of SMEs in social commerce platforms in a developing country. Method: This study employs a quantitative explanatory research design using survey data collected from 205 SMEs actively operating on TikTok and Shopee. The conceptual framework links short-video marketing and AI content tools to business performance through digital trust. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS to test both direct and mediating effects. Result: The results show that both short-video marketing and AI content tools have significant positive effects on digital trust, and digital trust has a strong positive effect on SME business performance. Furthermore, digital trust is proven to significantly mediate the relationships between short-video marketing and business performance, as well as between AI content tools and business performance. These findings highlight that trust is the key mechanism that transforms content strategies and technology adoption into performance outcomes. Future research is recommended to extend this model by incorporating additional variables such as platform reputation, influencer endorsement, or consumer digital literacy.